2019
DOI: 10.5204/ssj.v10i1.1098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating nursing students' engagement in an online course using flipped virtual classrooms

Abstract: Flipped classroom models allocate more time for active learning approaches compared with more traditional pedagogies, however what is less clear with the utilisation of flipped learning is evidence to support whether students in flipped classes are given more opportunities to develop higher order thinking skills (HOTs) to effect deep learning compared with the traditional ways of teaching. Focussing on this gap, this study compares on campus and off campus student engagement in two courses using different deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…Phillips and O'Flaherty, ( 2019 ) studied the concept of the virtual flipped classroom amongst university students. Although there was not significant difference found in student's academic performance when comparing the virtual flipped classroom to the traditional method of teaching for these nursing students, they did find that the course tutors played a large role.…”
Section: Teacher-student Interaction Of Vc Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Phillips and O'Flaherty, ( 2019 ) studied the concept of the virtual flipped classroom amongst university students. Although there was not significant difference found in student's academic performance when comparing the virtual flipped classroom to the traditional method of teaching for these nursing students, they did find that the course tutors played a large role.…”
Section: Teacher-student Interaction Of Vc Learningmentioning
confidence: 99%
“…Students did not have a positive tutor experience with the virtual flipped classroom approach and found that tutors were often underprepared and lacked training on how to use the virtual classroom effectively. Therefore, Phillips and O'Flaherty, ( 2019 ) advocated for more professional development for those staff who use the VC to maximise effectiveness for the students.…”
Section: Teacher-student Interaction Of Vc Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…This model enables students to enhance their learning process by active collaboration with their peers. FC leads to the greater involvement of students in high-quality active learning (Phillips and O'Flaherty, 2019). Also, studies show that by adopting the FC, instructors have more opportunity, flexibility and freedom to design the learning methods and enhance students' competency such as critical thinking and problem-solving ability (Flores I Alarcia et al, 2016).…”
Section: Background Work and Research Hypothesesmentioning
confidence: 99%
“…Prior to the pandemic, there were minimal examples of virtual flipped classroom use in the literature, for any discipline. 4 , 5 Previous work focused mostly on physical flipped classrooms, often with asynchronous online learning components. Some synchronous online course design research has been conducted, but there was scant evidence for also using a flipped classroom model in those studies.…”
Section: Introductionmentioning
confidence: 99%